QUALITY OF SERVICES PROVIDED BY STADIUM: A CASE STUDY OF TRAD STADIUM - เทียนบัญญัติ กรกนก; สราญรมย์ ดวงตา (Academic Journal Phranakhon Rajabhat University, 2018)
The purposes of this research were 1) to study service quality of Trad stadium perceived by customers 2) to compare service quality of Trad stadium by customers personal factors and 3) to study the relationship between customers expectations and their needs. The sample was 400 customers of Trad stadium. The research instrument was questionnaire. The statistics of this research were frequency, percentage, mean, Standard Deviation (SD), t-test, One-way ANOVA, and Pearson’s Correlation Coefficient. The results of the research were as follow: Overall, the service quality of Trad stadium was at a high level. The service quality in understanding and recognizing customers was at the highest, and the service quality in confident, tangibleness, respectiveness, reliability, and responsibility were at the least important respectively. Female customers had the higher level of service quality; in term of reliability and confident than male. Male customers had the higher level of service quality, in term of responsibility than female. A comparison of customers ages was found that it is significantly at .05 in all factors in service quality of Trad province stadium. The customers who were in the different educational background had different opinion towards service quality in term of tangibleness, reliability, and responsibility. The customers who different in occupations and salaries had a different opinion on service quality in term of tangibleness, reliability, responsibility, understanding and recognizing customers, which was significantly different at .05 level. The study of the relationship between customer quality expectations and needs of Trad the stadium, in overall factors, were found, that the relationship was at a low level (r = .233). There was the highest level of responsibility service quality (r = .347).